A call to reframe gifted education as maximizing learning. (December 2020) - Dixson, Dante D.; Peters, Scott J.; Makel, Matthew C.; Jolly, Jennifer L.; Matthews, Michael S.; Miller, Erin M.; Rambo-Hernandez, Karen E.; Rinn, Anne N.; Robins, Jennifer H.; Wilson, Hope E.
Schools exist to educate, yet the emphasis on age-based, grade-level standards fails to account for the wide range of academic readiness that exists in every classroom. Special education programs exist to meet student needs; gifted education should be no different. The authors, all gifted education researchers, present a vision for a model of gifted education that is aligned with Response to Intervention and personalized learning. At its heart, it is concerned with addressing the real-time academic needs of every student, with the ultimate goal of maximizing the learning of every student .